The queen of salsa [compact disc] - Cruz, Celia; Pacheco, Johnny; Colón, Willie, 1950-2026; Puente, Tito, 1923-2000 (Craft Recordings, 2025)
A Celia Cruz centennial tribute that features 12 of the salsa icon's indelible hits from her crowning years (1966-1993). The compilation brings together solo and collaboration songs featuring Latin music icons Tito Puente, Johnny Pacheco, Willie Colón and the Fania All Stars. Highlights include the quintessential rumba Quimbara; the salsa jam Usted abusó; and the salsafied guajira-son Guantanamera.